Alkaloids of dendrobium nobile lindl. Altered hepatic lipid homeostasis via regulation of bile acids. (15th September 2019) - Huang, Si; Wu, Qing; Liu, Hao; Ling, Hua; He, Yuqi; Wang, Changhong; Wang, Zhengtao; Lu, Yanliu; Lu, Yuanfu
Abstract: Ethnopharmacological relevance: Accumulation of hepatic lipid promotes systemic metabolic dysfunction and results in fatty liver. Our previous studies have shown that the alkaloids of Dendrobium nobile Lindl. (DNLA) could regulate the lipid metabolism gene expression in livers of mice. However, the protective effects on hepatic lipid homeostasis and the underlying mechanisms are still unclear. Materials and methods: The C57BL/6 male mice were randomly divided into four groups, including control group, model group, DNLA treatment group, and simvastatin positive control group. Mice in the control group and the other three groups were fed with control diet and high fat diet during the full course of this study, respectively. Hepatic lipid accumulation was induced by HFD in mice after 18 weeks of feeding. DNLA (15 mg/kg) and simvastatin (20 mg/kg) were administrated intragastrically in the DNLA treatment group and simvastatin positive control group for another 18 weeks, respectively. HE staining and Oil-Red-O staining of liver tissues were observed. TC and TG levels in liver were assayed. The amount of major bile acids in mice livers were quantified by UPLC-MS. Expression levels of genes were tested by the real-time PCR. Results: The results of HE staining and Oil-Red-O staining showed that DNLA could improve hepatic lipid homeostasis. DNLA significantly decreased liver TC and TG levels in the DNLA group. Moreover, the UPLC-MS analysis showed that DNLA did not only influence the hepatic bile acid quantity but did raise the hydrophilicity. Compared with the model group, DNLA decreased the hepatic levels of several free bile acids, including LCA, DCA, CA, and CDCA, and increased most important taurine-conjugated bile acids levels in liver, including TMCAs, TCDCA, TUDCA, and THDCA. In addition, DNLA also decreased the CA/CDCA ratio. The gene expression levels of Cyp27a1, Cyp3a11, Fxr, and Shp were up-regulated in DNLA treatment group. Conclusion: DNLA may improve the hepatic abnormal lipid profile of HFD-fed mice via two pathways: (1) enhancing the taurine-conjugated bile acids which are highly hydrophilic and contribute to the excretion of cholesterol; (2) decreasing the CA/CDCA ratio which is positively related to cholesterol absorption. Graphical abstract: Image 1